Role of Fragmentation at the Production Level of a Sublevel Caving Operation - Manzoor, Sohail (Luleå tekniska universitet, Geoteknologi, 2023)
This research was conducted to evaluate the association of rock fragmentation with different unit operations of a sublevel caving (SLC) production cycle. Drilling, charging, and blasting, as well as the nature of the rock mass, can affect the fragmentation observed at the drawpoints. Similarly, loading the blasted material from the drawpoints and dumping to the orepasses are strongly influenced by the nature of the fragmentation, particularly the oversize rock fragments. The aim of this research was to evaluate the operational and economic impacts of different fragment sizes in a production cycle of an SLC operation. It also investigated the possibility of predicting rock fragmentation in SLC blasting based on the nature of the rock mass. The required data for this research were collected from LKAB’s Malmberget iron ore mine. The loading operation of the blasted rock was filmed, and images of Load-Haul-Dump (LHD) buckets containing blasted rock were extracted from the video recordings. The blasted rock inside the buckets was categorized as fine, medium, coarse, and oversize fragmentation, based on the median fragment size (X 50 ). Measurement While Drilling (MWD) data were used to classify the rock mass based on the extent of rock fracturing, and statistical analysis was performed to predict the fragmentation. The results showed that the percentage occurrence of fine and medium fragmentation classes and oversize fragments have better correlations and can be better predicted using MWD data than other fragmentation types. The impact of dumping oversize fragments to orepasses with and without a screening device was evaluated. The results showed an increase in the cycle time of the LHD machines for the orepass with the screening infrastructure. The results suggest that the drill monitoring technique has the potential to predict rock fragmentation, particularly oversize rock fragments. In addition, the variations in fragmentation during loading should be considered to allocate the best resources for handling ...